Phytochemical Profiling and Nutritional Assessment of Artemisia herba-alba, Arbutus pavarii, and Annona cherimola from Selected Libyan Regions - Khadijah Al-Awjali; Farag El-Mokasabi; Hamad Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
The contents of anti-oxidant capacity, total phenol content, mineral concentration, total carbohydrate, and Phytochemical screening of Artemisia herba alba Asso, Arbutus pavarii Pamp, and Annona cherimola Mill were selected from some eastern regions of Libya. The results of this study recorded that the contents of phenols and antioxidant activity were fluctuated in the ranges of (176.01 – 332.046) and (9.42 – 10.64 ppm), respectively. For Carbohydrate, the results showed small amounts in most studied plants in this study, its values ranging between (0.024-0.461) and (0.11-0.142 ppm) for leaves and stems, respectively. For the phytochemical screening, the results of this study showed the presence of different natural product compounds as sterols, flavonoids, alkaloids, tannins, anthraquinones, saponins, and phenols. Also, the results exhibited variations in the contents of these compounds between the selected plants and between leaves and stems. The detection of sterols, flavonoids, alkaloids, tannins, anthraquinones, saponins, and phenols was applied by Color tests according to standard methods. For Potassium, from (1.76 -34.16 ppm) for leaves and from (48.56-84.36 ppm) for stems. For Sodium (0.291-1.375 ppm) for leaves and from (3.48-8.28 ppm) for stems. And for Calcium from (0.08-0.48 ppm) for leaves and from (0.291-0.958 ppm) for stems.